Roma Cumhurı̇yetı̇nde İ.Ö.133-İ.Ö.27 yılları arasında Asia Eyaletı̇ - Güney, Emre Mirza (My University, 2025)
Çalışma I. Pön Savaşı ve Roma’nın Batı Akdeniz’deki hâkimiyet süreci ile başlamaktadır. Zira bu yıldan Asia Eyaleti’nin kurulduğu İ.Ö. 133 yılına kadar olan aralık, Roma’nın Anadolu politikasını anlamak açısından önemlidir. İ.Ö. 133 yılında Pergamon Kralı III. Attalos’un ölümü ile Roma, Anadolu’ya ilk kez yerleşmiş ve burada bir provincia kurmuştur. Bu provincia son Pergamon kralı III. Attalos’un vasiyetiyle gerçekleşmiştir. Elimizdeki kaynaklar ve görüşler ise vasiyetin doğruluğunun tartışmalı olduğunu göstermektedir. Bu noktada vasiyetin ve içeriğinin doğruluğu ve eğer doğru değilse Roma’nın neden böyle bir araca ihtiyaç duyduğu ile ilgili tartışmalar ortaya çıkmıştır. Ayrıca bu gelişme Roma’nın Anadolu’da fizikî bir hâkimiyet kurması açısından önemlidir. Bu durum Anadolu dinamiklerinde pek çok dönüşümün yaşanmasına yol açmıştır. Çalışmada III. Attalos’un vasiyeti, Roma’nın Anadolu’ya yerleşme politikası ve neden bu tarihte gerçekleştiği, Anadolu halkı ile Roma arasındaki gelişmeler gibi unsurlar ve bağlantıların kurulabilmesi açısından Roma kentinde yaşanan gelişmelerle birlikte geniş bir profil çizilmeye çalışılmıştır. Çalışmada Roma’nın iç dinamikleri göz önünde bulundurularak, Anadolu’da izlediği politika üzerine tartışmalara yer verilmiştir. Bu tartışmalardan biri, III. Attalos’un vasiyetinin yanı sıra, Roma’nın Anadolu’ya girişinin neden bu tarihe denk geldiği hakkındadır. Çalışmada bu konu Roma’nın Akdeniz’deki rakipleri ve onlarla olan ilişkisine odaklanarak farklı bir perspektif çizmeyi amaçlamıştır. Bu perspektif Roma Senatosu’nun tavrı ve Roma’nın iç dinamiklerinde yaşanan gelişmelerle beraber incelenerek Roma’nın, Anadolu’daki politikası ele alınmıştır. Bunların yanı sıra Roma’nın, Magnesia Savaşı’ndan sonra Anadolu’daki “hakemlik” süreci, bu süreçte izlediği politika ve Asia Eyaleti’nin kurulması noktasında Anadolu krallıklarının ve halklarının tepkileri üzerinde durulmuştur.

This study begins with the First Punic War and the process of Rome's establishment of dominance in the Western Mediterranean. The period between this conflict and the foundation of the province of Asia in 133 BCE is crucial for understanding Rome’s policy toward Anatolia. In 133 BCE, following the death of King Attalos III of Pergamon, Rome established its first province in Anatolia. This development was ostensibly made possible by the will of the last Pergamene king, Attalos III. However, existing sources and scholarly opinions indicate that the authenticity of this will is a matter of debate. At this point, discussions have emerged regarding the veracity of the testament and, if it was indeed fabricated or manipulated, why Rome might have felt the need to employ such an instrument. This development is particularly significant in terms of Rome’s establishment of a physical presence in Anatolia, which triggered a number of transformative shifts within the region's political and social dynamics. The study seeks to provide a comprehensive analysis of Attalos III’s will, Rome’s settlement policy in Anatolia, and why this process occurred at that particular moment in time. In doing so, it explores not only local developments but also situates these within the broader context of events unfolding in Rome itself. By taking into account Rome’s internal dynamics, the study engages in a critical discussion of the Republic’s policies in Anatolia. One of the central debates concerns not only the testament of Attalos III but also the question of why Rome’s entry into Anatolia occurred specifically at this historical juncture. This issue is addressed through a new perspective that considers Rome’s relations with its Mediterranean rivals. In this context, the study examines Rome’s Anatolian policy in relation to the stance of the Roman Senate and internal developments within the Republic. Additionally, the analysis focuses on Rome’s role as an “arbiter” in Anatolia following the Battle of Magnesia, the nature of its policies during this period, and the responses of the Anatolian kingdoms and populations to the eventual establishment of the province of Asia.
Keywords: Ancient history; Asia Eyaleti; Attalos’un Vasiyeti; Bequest of Attalos; Eskiçağ tarihi; Geç Roma Cumhuriyeti; History; Late Roman Republic; Pergamon; Province of Asia; Roma; Roma Anadolu’su; Roman Anatolia; Rome; Tarih